Taxonomic notes on the Lygephila vulcanea (Butler, 1881) species-group (Lepidoptera, Erebidae, Toxocampinae) - Pekarsky, Oleg (Zootaxa, 2016)
Present paper is dedicated to taxonomic clarification of L. vulcanea and L. lupina (=mirabilis Bryk, 1948, syn. rev.) initiated in a previous publication (Pekarsky 2014). The distribution patterns of the two species are discussed, disputing the presence of L. vulcanea in Russia.